O ensino a distância do conceito de medida baseado na Sequência Fedathi - Carmo, Fernanda Maria Almeida do (2022)
The computerization of society, within the scope of digital technologies, has brought new paradigms to education, increasing the teaching modality Distance Education. The teaching programs have space to present their own designs, languages and educational and technological resources. In this perspective, Distance Education of the Laboratório MultiMeios stands out, based on the teaching methodology Sequência Fedathi. In the case of mathematics teaching, in this proposal of Distance Education, there is still not ample knowledge and consolidated knowledge. Thus, the objective of this research is to develop a proposal for distance learning of the concept of Measure, based on the Sequência Fedathi. This research has a qualitative character and, from the method perspective, it is classified as exploratory research, also using the Sequência Fedathi research methodology. Thus, a didactic proposal was developed for the distance learning of the concept of Measure, as well as a didactic design in the Virtual Teaching Environment Moodle MultiMeios. With this research, a reorganization of the Measure contents was observed, constituted by the concepts of Magnitude, Area and Volume, and a different didactic approach was obtained from the treatment usually given, based on the Measure Theory and the Situação Generalizável principle. Didactic material was also produced, based on the elaboration of didactic sessions on each of the aforementioned themes. It was also identified that the choice of tools in virtual environments should take into account, mainly, interaction, such as the TeleMeios and the Forum. It was concluded that the Sequência Fedathi allows the conceptual and progressive construction with the active participation of the student throughout the course and that it is the teacher's mediation that makes all the difference, regardless of the environment, technology, means and resources used.